Impact of time point of extracorporeal membrane oxygenation on mortality and morbidity in congenital diaphragmatic hernia: a single-center case series - Wegele, Christian; Schreiner, Yannick; Perez Ortiz, Alba; Hetjens, Svetlana; Otto, Christiane; Boettcher, Michael; Schaible, Thomas; Rafat, Neysan (Children, 2022)
Since there are no data available on the influence of the time point of ECMO initiation on morbidity and mortality in patients with congenital diaphragmatic hernia (CDH), we investigated whether early initiation of ECMO after birth is associated with a beneficial outcome in severe forms of CDH. All neonates with CDH admitted to our institution between 2010 until 2020 and undergoing ECMO treatment were included in this study and divided into four different groups: (1) ECMO initiation < 12 h after birth (n = 143), (2) ECMO initiation between 12-24 h after birth (n = 31), (3) ECMO initiation between 24-120 h after birth (n = 48) and (4) ECMO initiation > 120 h after birth (n = 14). The mortality rate in the first (34%) and fourth group (43%) was high and in the second group (23%) and third group (12%) rather low. The morbidity, characterized by chronic lung disease (CLD), did not differ significantly in the three groups; only patients in which ECMO was initiated >120 h after birth had an increased rate of severe CLD. Our data, although not randomized and limited due to small study groups, suggest that very early need for ECMO and ECMO initiation > 120 h after birth is associated with increased mortality.